Modeling the ligand specific m- and d-opioid receptor conformations - MILAN SENĆANSKI; MILOVAN D. IVANOVIĆ; SONJA VUČKOVIĆ; LJILJANA DOŠEN-MIĆOVIĆ (Journal of the Serbian Chemical Society, 2011)
An automated docking procedure was applied to study the binding of a series of m- and d-selective ligands to ligand-specific m- and d-opioid receptor models. Short-time molecular dynamic simulations were used to obtain ligand-specific m- and d-opioid receptors from arbitrarily chosen models of the active form of these receptors. The quality of receptor model depended on the molecular volume of the ligand in the receptor–ligand complex used in the molecular dynamic simulations. Within a series of ligands of similar size (volume), the results of ligand docking to the obtained ligand–specific receptor conformation were in agreement with point mutation studies. The correlation of the calculated and the experimentally determined binding energies was improved in relation to the initial receptor conformation.